2018
DOI: 10.1016/j.prnil.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

To investigate the correlation between the visual prostate symptom score, the international prostate symptom score, and uroflowmetry parameters in adult Thai males of different educational levels

Abstract: BackgroundTo evaluate the correlation between the International Prostate Symptom Score (IPSS), Visual Prostate Symptom Score (VPSS), and uroflowmetry parameters in Thai males and to examine the possibility in establishing a severity cut-off point for VPSS.MethodsBetween 1st February and 31st May 2016 a total of 200 men were enrolled onto the study and divided into high and low educated groups. All of them were requested to complete paperwork including their personal data, and then to complete a VPSS and IPSS q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 15 publications
4
14
1
Order By: Relevance
“…A result in our study that does not coincide with what has been published about these two scales, is that we did not find a significant correlation between VPSS and Qmax, nor between IPSS and Qmax; as in the study published by Setthawong et al (8) where VPSS did have a statistically significant correlation with uroflowmetry rate, residual urine and prostate size than IPSS.…”
Section: Discussioncontrasting
confidence: 95%
“…A result in our study that does not coincide with what has been published about these two scales, is that we did not find a significant correlation between VPSS and Qmax, nor between IPSS and Qmax; as in the study published by Setthawong et al (8) where VPSS did have a statistically significant correlation with uroflowmetry rate, residual urine and prostate size than IPSS.…”
Section: Discussioncontrasting
confidence: 95%
“…In the other direction, this research had no correlation to frequency score between the IPSS and VPSS in the low-educated group, but the study showed a significant correlation to frequency score between the IPSS and mVPSS in all patients, which is the same as the previous research, "To investigate the correlation between the visual prostate symptom score, the international prostate symptom score, and uroflowmetry parameters in adult Thai males of different educational levels," a study by Setthawong, V. et al 7 . In addition, we found out that the loweducated group required more assistance to complete the IPSS, VPSS and mVPSS questionnaires than the high-educated group, and most patients mentioned that the mVPSS was easier to understand and needed less time to be completed.…”
Section: Discussionsupporting
confidence: 55%
“…On the other hand, in Thailand, Pim-pon Hongthong found that the VPSS was statistically significantly related to the IPSS only in high-educated Thai patients 6 . Moreover, Vasun Setthawong, et al showed that the VPSS was statistically significantly related to the IPSS and uroflowmetry parameters but surprisingly low-educated patients felt that the IPSS was easier than the VPSS 7 . For these reasons, the modified visual prostate symptom score (mVPSS) was created by this study according to the VPSS.…”
Section: Introductionmentioning
confidence: 99%
“…Men with limited education can complete the VPSS faster and unassisted compared to the IPSS. The VPSS has seen increasing study in recent years, with good correlation to the IPSS demonstrated in countries including Thailand, 59 India, 60 Turkey, 61 Indonesia, 62 Uganda, 63 South Africa 64 and South Korea 65 …”
Section: Discussionmentioning
confidence: 99%